Answer:
Option A is correct
[tex]3(\frac{x}{4})-\frac{1}{2}(\frac{x}{10})[/tex]
Step-by-step explanation:
Given that:
70% of x.
⇒[tex]\frac{70}{100} \times x[/tex]
⇒[tex]\frac{7x}{10}[/tex]
Option A:
[tex]3(\frac{x}{4})-\frac{1}{2}(\frac{x}{10})[/tex]
⇒[tex]\frac{3x}{4}-\frac{x}{20}[/tex]
⇒[tex]\frac{60x-4x}{80}[/tex]
⇒[tex]\frac{56x}{80}[/tex]
Simplify:
⇒[tex]\frac{7x}{10}[/tex]
Option B:
[tex]3(\frac{x}{4})-(\frac{x}{10})[/tex]
⇒[tex]\frac{3x}{4}-\frac{x}{10}[/tex]
⇒[tex]\frac{30x-4x}{40}[/tex]
⇒[tex]\frac{26x}{40}[/tex]
Simplify:
⇒[tex]\frac{13x}{20}[/tex]
Option C:
[tex](\frac{x}{2})+(\frac{x}{10})[/tex]
⇒[tex]\frac{6x}{10}[/tex]
Simplify:
⇒[tex]\frac{3x}{5}[/tex]
Option D:
[tex](\frac{x}{2})+\frac{1}{2}(\frac{x}{4})[/tex]
⇒[tex]\frac{x}{2}+\frac{x}{8}[/tex]
⇒[tex]\frac{5x}{8}[/tex]
Therefore, only option which is equivalent to 70% of x is, Option A i.e [tex]3(\frac{x}{4})-\frac{1}{2}(\frac{x}{10})[/tex]